Gender differences in risk behaviour: does nurture matter? - Alison L. Booth; Patrick J. Nolen (Institute for the Study of Labor (IZA), 2009)
Women and men may differ in their propensity to choose a risky outcome because of innate preferences or because their innate preferences are modified by pressure to conform to gender-stereotypes. Single-sex environments are likely to modify students' risk-taking preferences in economically important ways. To test this, our controlled experiment gave subjects an opportunity to choose a risky outcome - a real-stakes gamble with a higher expected monetary value than the alternative outcome with a certain payoff - and in which the sensitivity of observed risk choices to environmental factors could be explored. The results show that girls from single-sex schools are as likely to choose the real-stakes gamble as much as boys from either coed or single sex schools, and more likely than coed girls. Moreover, gender differences in preferences for risk-taking are sensitive to the gender mix of the experimental group, with girls being more likely to choose risky outcomes when assigned to all-girl groups. This suggests that observed gender differences in behaviour under uncertainty found in previous studies might reflect social learning rather than inherent gender traits.
urn:nbn:de:101:1-20090306199
Keywords: C9; C91; C92; J16; 330; Gender identity; controlled experiment; risk aversion; risk attitudes; single-sex schooling; coeducation; Risikopräferenz; Geschlecht; Soziale Beziehungen; Frauenbildung; Test; Großbritannien